Fabrication of Activated Carbon Decorated with ZnO Nanorod-Based Electrodes for Desalination of Brackish Water Using Capacitive Deionization Technology - Martinez, Jhonatan (2023)
Capacitive deionization (CDI) is a promising and cost-effective technology that is currently being widely explored for removing dissolved ions from saline water. This research developed materials based on activated carbon (AC) materials modified with zinc oxide (ZnO) nanorods and used them as high-performance CDI electrodes for water desalination. The as-prepared electrodes were characterized by cyclic voltammetry, and their physical properties were studied through SEM and XRD. ZnO-coated AC electrodes revealed a better specific absorption capacity (SAC) and an average salt adsorption rate (ASAR) compared to pristine AC, specifically with values of 123.66 mg/g and 5.06 mg/g/min, respectively. The desalination process was conducted using a 0.4 M sodium chloride (NaCl) solution with flow rates from 45 mL/min to 105 mL/min under an applied potential of 1.2 V. Furthermore, the energy efficiency of the desalination process, the specific energy consumption (SEC), and the maximum and minimum of the effluent solution concentration were quantified using thermodynamic energy efficiency (TEE). Finally, this work suggested that AC/ZnO material has the potential to be utilized as a CDI electrode for the desalination of saline water.